The effectiveness of Moodle among engineering education college students in Indonesia - Muhammad Amin; Abdul Muin Sibuea; Bima Mustaqim (Institute of Advanced Engineering and Science, 2023)
The selection of learning media in accordance with the subject will greatly affect the interest and response of students in attending learning. In addition, during the COVID-19 pandemic, learning is conducted online, many students are not serious and are not interested in attending learning. Therefore, it is necessary to have media or online lecture platforms that can attract students’ attention, so that students can follow and be interested in learning. The purpose of this study was to look into the impact of Moodle on the research methodology performances of college students in Indonesia. Its goal was to investigate college students’ reactions to Moodle as an innovative online platform. This study included 86 Indonesian college students who sat in a single intact group. Based on the quantitative data, the study used a quasi-experimental design and a one-group pretest-posttest design. A test and a questionnaire were used to collect data. According to the study’s findings, Moodle improved Indonesian students’ research methodology performance. Students were excited to use Moodle because of its simplicity, usefulness, and accessibility. Moodle’s effectiveness in other contexts should be investigated in future research. This study confirmed Moodle's dependability in broader contexts.